Ethno-Ornithology of the Mushere of Nigeria: Children’s Knowledge and Perceptions of Birds - Pam, Grace Alheri-Bulus; Zeitlyn, David; Gosler, Andrew (Ethnobiology Letters, 2018)
Mushere children’s ethno-ornithology was surveyed from October to November 2015 to find out their level of bird knowledge—as well as whether and how children valued and learned about birds—in order to determine the potential role such knowledge might play in Mushere biodiversity conservation. Methods included picture elicitation exercises, free-listing, and semi-structured interviews. Our results revealed a limited knowledge of birds in Mushere children, and that bird knowledge was gendered. Girls learned through observation, while boys learned through practical bird-related activities. Learning was mostly horizontal for boys but vertical and/or oblique for girls; the most reported learning mode was through oral tradition. Farmland and garden birds were the most common groups, with birds in the families Columbidae and Estrildidae having the highest salience and frequency of mention. We suggest that this reflects the importance of ecological salience, since both groups are relatively locally abundant. The children also had a limited knowledge of cultural beliefs and uses of the birds, but valued birds as important. We argue that how much children will know and learn about any biological domain will be determined by the cultural attitudes and perceptions of that domain, and the cultural importance attached to it. We conclude that the limited knowledge of birds in Mushere children reflects Mushere cultural indifference (ornithoapatheia) to birds. We suggest that a consistent and deliberate conservation education program that will work towards encouraging ornithophilia, the love of birds, and biophilia, the love of nature, in Mushere children could be beneficial.